14.1% CsPbI3 Perovskite Quantum Dot Solar Cells via Cesium Cation Passivation. Issue 28 (23rd June 2019) - Ling, Xufeng; Zhou, Sijie; Yuan, Jianyu; Shi, Junwei; Qian, Yuli; Larson, Bryon W.; Zhao, Qian; Qin, Chaochao; Li, Fangchao; Shi, Guozheng; Stewart, Connor; Hu, Jiaxin; et al.
Abstract: Surface manipulation of quantum dots (QDs) has been extensively reported to be crucial to their performance when applied into optoelectronic devices, especially for photovoltaic devices. In this work, an efficient surface passivation method for emerging CsPbI3 perovskite QDs using a variety of inorganic cesium salts (cesium acetate (CsAc), cesium idodide (CsI), cesium carbonate (Cs2 CO3 ), and cesium nitrate (CsNO3 )) is reported. The Cs‐salts post‐treatment can not only fill the vacancy at the CsPbI3 perovskite surface but also improve electron coupling between CsPbI3 QDs. As a result, the free carrier lifetime, diffusion length, and mobility of QD film are simultaneously improved, which are beneficial for fabricating high‐quality conductive QD films for efficient solar cell devices. After optimizing the post‐treatment process, the short‐circuit current density and fill factor are significantly enhanced, delivering an impressive efficiency of 14.10% for CsPbI3 QD solar cells. In addition, the Cs‐salt‐treated CsPbI3 QD devices exhibit improved stability against moisture due to the improved surface environment of these QDs. These findings will provide insight into the design of high‐performance and low‐trap‐states perovskite QD films with desirable optoelectronic properties. Abstract : This work reports an efficient post‐treatment method for CsPbI3 perovskite quantum dots (QDs) using cesium cations, which can passivate the CsPbI3 surface and improve the electron coupling of QDs. Finally, the best CsPbI3 QD solar cell with an impressive efficiency of 14.10% is achieved by cesium acetate (CsAc) and exhibits improved stability against moisture.